Leukocyte Count: A Reliable Marker for Severity of Organophosphorus Intoxication - Farhat Ul Ain, Muhammad Sarfraz, Muhammad Khurram, Unaiza Sharif, Mudassar Latif Malik, Nida Anjum, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: To determine reliability of leukocyte count on admission for prediction of mortality among patients with organophosphorus intoxication. Early prediction can help in preventing the poor outcome and improved management. This is cost and time effective method and better management and preventive protocols can be developed. Objective: To determine the diagnostic accuracy of leukocyte count in prediction of mortality in patients with organophosphorus intoxication keeping actual mortality as gold standard. Material and Methods: The design of this study was a Cross sectional study design. The duration of this study was six months from 31-03-2020 to 30-09-2020 and this study was conducted in the Department of Medicine (unit II), HFH, Rawalpindi. A total of one hundred and sixty (n=160) patients of either gender between age between 16-85 years who were confirmed cases of organophosphorus poisoning were enrolled. Leukocyte count levels were noted at the time of admission and patients were monitored for 7 days in the hospital for mortality. Results: The results showed that sensitivity, specificity, positive predictive value, negative predictive value and accuracy of raised leukocytes counts (>12000/uL) at admission as 60.4%, 77.8%, 50.0%, 84.3% and 73.1% respectively. ROC curve showed best cutoff value of raised leukocytes counts (>12000/uL) at admission as 10253/uL, where sensitivity of 72.1% and specificity of 58.1% was achieved. Area under the curve (AUC) was calculated as 0.707. Practical Implication: To determine the diagnostic accuracy of leukocyte count in prediction of mortality in patients with organophosphorus intoxication keeping actual mortality as gold standard Conclusions: Raised leukocytes counts (>12000/uL) at admission allowed prediction of mortality in patients with organophosphorus poisoning with reasonable accuracy. Our study results showed sensitivity, specificity, PPV, NPV and accuracy of 60.4%, 77.8%, 50.0%, 84.3% and 73.1% respectively. Keywords: Leukocyte Counts, Organophosphorus, Poisoning, Mortality, Intoxication, Predictive Value, Morbidity.